Guru di Persimpangan Kurikulum Baru: Dilema Implementasi Kurikulum Merdeka Berbasis Keislaman - Susanna, Susanna; Usman, Jarjani; Suyanta, Sri (Fitrah: Journal of Islamic Education, 2023)
This research aims to analyze the dilemmas faced by Islamic educational institutions that implement the independent curriculum. The focus of the research is on implementation, and obstacles to maintaining Islamic characteristics in the latest curriculum. The research method used is qualitative, based on literature study. The data source used is the results of relevant research related to the topic, which is tracked using the publish or ferish application with a total of fifty relevant texts. Data analysis using systematic literature review. The results revealed that the Implementation of Merdeka Curriculum in Islamic Education Institutions involves the process of adapting Islamic principles in curriculum development which focuses on religious values, morals, and Islamic science. This involves preparing learning materials, teaching methods, and evaluations that are in accordance with Islamic values as well as the needs and context of the Islamic education institution. The constraints of implementing an independent curriculum in Islamic education institutions include limited resources, institutional conservatism, incompatibility with local needs, teacher and staff readiness, community and parent reactions, and performance evaluation and monitoring.